Stereochemical significance of O to N atom interchanges within cationic helicenes: experimental and computational evidence of near racemization to remarkable enantiospecificity. Issue 29 (18th June 2019) - Labrador, Geraldine M.; Besnard, Céline; Bürgi, Thomas; Poblador-Bahamonde, Amalia I.; Bosson, Johann; Lacour, Jérôme
Abstract : Oxygen atoms of cationic dioxa and azaoxa [6]helicenes can be exchanged by amino groups and these reactions lead to either near racemization (es 3%) or to a remarkable enantiospecificity (es up to 97%). Based on detailed investigations, the chirality transfer of the first transformation can be improved to 61%. Abstract : Oxygen atoms of cationic dioxa and azaoxa [6]helicenes can be exchanged by amino groups to form azaoxa and diaza [6]helicenes respectively. The mild reaction conditions developed herein allow the construction of libraries of derivatives with sensitive and/or functionalized side chains. Using enantioenriched dioxa or azaoxa helicene precursors, these exchanges lead to either near racemization (es 3%) or to a remarkable enantiospecificity (es up to 97%). This unusual behavior is fully characterized via experimental and computational mechanistic evidence. Based on these investigations, the enantiospecificity of the first transformation can be improved to 57–61%.